Uma análise da expansão agrícola da soja no município de Santarém P A e seus im pactos socioterritoriais - GUIMARÃES, Edcley de Sousa (Universidade Federal do Oeste do Pará, 2023)
The present work analyzes the agricultural expansion of soy in the municipality of Santarém-Pará, and its socio-territorial impacts. Regarding the expansion of soy production in the Amazon, in the last twenty years there has been a significant growth of agricultural culture in the western region of Pará, with the municipality of Santarém highlighting its expansion and development. The general objective is to analyze the main socio-territorial impacts resulting from the agricultural expansion of soy in the municipality of Santarém, in the years 2000 to 2020. The methodology is based on a qualitative bibliographic reference work, with research on websites, theses, articles, monographs. It was observed that the expansion of soy was due to government incentives that the soy agribusiness overcomes barriers "created by the local society", having this mechanism to root its commercial practices in the region, in order to explore the entire area in its surroundings. In this way, it was highlighted how the expansion of this legume in Brazil, Amazonia and Pará, and especially in the Santaréne plateau, took place. It was observed in the development of the research that the production of soy in the Amazon makes the traditional peoples of the plateau area to leave their lands to go to live in urban areas. The results show that the performance of the multinational Cargill, the availability of land at low prices and the privileged location of the municipality of Santarém in relation to international markets were one of the main factors that influenced the arrival of soybeans to the region, as well as deforestation and imbalance. environmental impact in the Amazon region.